Modeling and computation in vibration problems. - Chakraverty, Snehashish; Tornabene, F.; Reddy, J. N. (Junuthula Narasimha), 1945- (IOP (Series). Release 21., 2021)
Vibration problems are commonly encountered in a wide range of scientific and technological domains. Covering the most recent computational and theoretical trends in the field, these books provide a state-of-the-art treatment of different mathematical theories of vibration, numerical simulations, machine intelligence techniques and physical experiments with computational investigations, as well as their various engineering, biological and science applications.